3C-like protease inhibitors against coronaviruses - Perera, Krishani Dinali Imasha (Kansas State University, 2018)
Coronaviruses are pathogens that cause diverse diseases in humans and animals. The studies in this dissertation are focused on feline coronavirus (FCoV), ferret coronavirus (FRCoV) and mink coronavirus (MCoV). FCoV and FRCoV infections typically cause enteritis in cats and ferrets, respectively. However, a 100% fatal systemic disease called feline infectious peritonitis (FIP) can develop in some FCoV infected cats and a fatal systemic disease resembling FIP can develop in some FRCoV infected ferrets. MCoV causes enteritis which results in significant economic loss to mink farmers. No effective vaccine or treatment is available despite the increasing importance of these viral diseases. We have previously reported the synthesis of inhibitors against 3C-like protease (3CLpro) of FCoV and demonstrated the antiviral efficacy of a 3CLpro inhibitor for treating FIP. FRCoV and MCoV 3CLpro are closely related to FCoV 3CLpro. Therefore, we investigated the structure-function relationships of our 3CLpro inhibitors to identify the struc-tural requirements of inhibitors for FRCoV and MCoV. This is the first report of antiviral com-pounds against FRCoV and MCoV. We have previously conducted a field trial with a potent 3CLpro inhibitor, GC376, in cats with naturally occurring FIP. Comparison of the FCoV 3CLpro amino acid sequences from the pre- and post-treatment samples in one cat showed amino acid changes in 3CLpro. Hence, we generated recombinant 3CLpros carrying the amino acid changes and characterized the effects of these amino acid changes in FCoV 3CLpro on its susceptibility to GC376. We observed that these amino acid changes did not markedly affect the activity of GC376 in fluorescence resonance energy transfer (FRET) assay, explaining the absence of clinical drug resistance in this cat during the field trial.
Keywords: 3C-like protease; Protease inhibitor; Feline coronavirus; Ferret coronavirus; Mink coronavirus